2000
DOI: 10.1055/s-2000-8387
|View full text |Cite
|
Sign up to set email alerts
|

How Should Dysphagia Care of Older Adults Differ? Establishing Optimal Practice Patterns

Abstract: An unprecedented demographic transformation is occurring as our population ages. Those older than age 65 represent the fastest growing segment of the population. Within this older group, approximately 10% to 30% of adults are estimated to have dysphagia, but true incidence and prevalence are unknown. They make up a heterogeneous mix of both healthy and disabled individuals that reside across a spectrum of living settings. As clinicians approach older adults with dysphagia, general geriatric principles should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 52 publications
2
93
0
8
Order By: Relevance
“…In addition, because our healthy control subjects were matched for age with our stroke group, the age range for our control group was fairly restricted (mean = 62 years, 62% were younger than age 65). Previous research has found that longer transit times and increased age are associated [19][20], and that in older populations, the point at which swallowing may differ notably from younger subjects is between the ages of 65 and 70 [21][22]. As such, a larger sample size that incorporates a greater number of healthy adults over the age of 65 may provide a more accurate range of normal transit times and better delineate dysphagia from normal variances in swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because our healthy control subjects were matched for age with our stroke group, the age range for our control group was fairly restricted (mean = 62 years, 62% were younger than age 65). Previous research has found that longer transit times and increased age are associated [19][20], and that in older populations, the point at which swallowing may differ notably from younger subjects is between the ages of 65 and 70 [21][22]. As such, a larger sample size that incorporates a greater number of healthy adults over the age of 65 may provide a more accurate range of normal transit times and better delineate dysphagia from normal variances in swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia can occur due to a range of medical conditions, including premature birth, cerebral palsy, Alzheimer's disease, cancer of the oesophagus, Parkinson's disease and stroke (Althaus, 2002, Vivanti et al, 2009). It affects individuals of all ages (Whelan, 2001, Saigal andDoyle, 2008), but commonly with the elderly where their swallowing difficulty arises due to illness, polypharmacy and weakened reserves (Barczi et al, 2000, Cabre et al, 2010.…”
Section: Dysphagiamentioning
confidence: 99%
“…의 40~60%가 연하 장애를 갖고 있는 것으로 보고되고 있다 (Barczi, Sullivan, & Robbins, 2000). 우리나라의 경우 전국 적인 자료는 없으나 요양시설노인의 10~30% 정도가 연하장애 로 인한 건강문제를 가지고 있는 것으로 추정되었으며 (Choi, 2009), 2010년 대도시 소재 두 곳의 노인요양시설 거주 노인 전수를 대상으로 한 연구에서는 노인의 52.7%가 연하장애가 있는 것으로 보고되었다 .…”
unclassified